Determination of paraquat (Herbicide) residue level in sandy clay loam soil using high performance liquid chromatograph - Wong Yee Ching; N. Norsyamimi (Lifescience Global, 2013)
Pesticide is considered as the most widely used form of agricultural chemical. Pesticide residue is the remaining pesticide on or in soil after pesticide is applied on agriculture soil. Soil is a component that is crucial to life. The research purposely concerned on major effects that could be contributed from medium to unlimited application of pesticide. The soil samples were systematically collected from 5 plots and Paraquat residues concentrations were determined in dissimilar depth of soil layers. The herbicide used was Paraquat that contained Paraquat Dichloride. High Performance Liquid Chromatography (HPLC) analysis detected the peak area volumes of Paraquat in soil samples at level ranging from 0.3 to 5.9 mg/l. The concentration of Paraquat in sandy clay loam soil showed that herbicide leached downward to the depth of 15 cm. The maximum concentration of Paraquat residue was detected at 0 to15 cm of soil depth at 2.783 mg/l. In highly organic soils, adsorption is weaker and Paraquat remains herbicidally active for longer, up to 29 days in one trial on soil with 98% organic matter [1]. Oral dose, LD50 for human is equal to 40-60 mg/kg [2] while the lowest fatal dose recorded for human was 17 mg/kg, but even lower doses may be fatal for children [3].